Blue light driven free-radical polymerization using arylazo sulfones as initiators. Issue 40 (5th October 2021) - Nitti, Andrea; Martinelli, Angelo; Batteux, Fabrice; Protti, Stefano; Fagnoni, Maurizio; Pasini, Dario
Abstract : The polymerization of a broad range of electron-poor olefins has been achieved under free-radical conditions by using arylazo sulfones as visible light photoinitiators. Abstract : The polymerization of a broad range of electron-poor olefins has been achieved under free-radical conditions by using arylazo sulfones as visible light photoinitiators. The process proceeds smoothly at room temperature both in bulk and in the presence of solvents upon irradiation with a 40 W Kessil lamp (456 nm, blue light) in the absence of any co-initiators or additives. High molecular weight polymers are obtained in excellent yields.